Model for geometry optimisation of thermoelectric devices in a hybrid PV/TE system. (March 2016) - Hashim, H.; Bomphrey, J.J.; Min, G.
Abstract: A model for the geometry optimisation of thermoelectric devices in a hybrid photovoltaic - thermoelectric (PV/TE) system is presented. The model can be used to determine the optimal geometry of thermoelectric modules at which the maximum power output is achieved. The results of simulation using this model shows that an increase in both the overall power output and conversion efficiency may be achieved by incorporating a thermoelectric generator (TEG) to harvest waste heat from photovoltaic cell. In addition, the results demonstrate that the geometry optimisation also needs to consider the "trade-off" between achieving a large power output and minimising the consumption of thermoelectric materials. Highlights: Geometry optimisation of thermoelectric devices in hybrid PV/TE systems. Simulation under closed-circuit condition and various operating atmospheres. Determination of the overall power and efficiency of hybrid PV/TE systems. Evaluation of the benefits of hybrid PV/TE systems. Optimisation considering the "trade-off" between performances and material consumption.